Students’ Perception of the Use Podcast in Speaking Ability in Learning Speaking - Syafira Tri Ananda; Syafryadin (JPG: Jurnal Pendidikan Guru, 2025)
This research aimed to find out students’ perception of the use podcast in speaking ability in learning speaking and to know positive or negative response students’ of using podcast. The reserachers used a quantitative research design as a methodogy. The instrument for collecting data in this study is questionnaire, adapted from the work of Bawanti & Arifani (2021).The sample of this research is fourty three students from class A these students are specifically from the pool of first-semester students at the Faculty of Animal Husbandry at Bengkulu University during the academic year 2023–2024 It uses a Likert Scale with four distinct categories: "Strongly Agree", "Agree", "Disagree", and "Strongly Disagree". This research is a quantitative research and therefore uses Microsoft Excel as a tool to calculate the data that has been obtained. The findings of this research is that students agree that podcast can help them to learn English and students also have a positive opinion on podcasts in other words podcasts are learning media that have a positive side for students and also they are motivated to want to learn English better after using podcasts.